Assessment of Genetic Diversity of Narra (Pterocarpus indicus Willd.) Populations From Various Seed Sources in the Philippines Using RAPD - Delos Reyes, Maria Theresa (Journal of Environmental Science and Management, 2016)
Pterocarpus indicus Willd. (narra), a critically endangered group, is one of the priority species for conservation and reforestation in the Philippines due to its economic, industrial, and ecological importance. A range of 29 to 40 individual samples from each of six seed sources from the Philippines were tested for genetic diversity using 11 RAPD markers. A total of 134 loci were detected, 129 of which were polymorphic. The mean genetic diversity within population was found to be moderate at 0.3183, which could be attributed to the deciduous and outcrossing nature of narra. The genetic differentiation among populations (0.0575) and Wright’s Fixation Index (0.1528) suggests nearness of the populations to each other and distance from fixation of alternative alleles in the populations. The genetic distance and cluster analysis did not conform to geographical distribution, but revealed the relationships and the possible origin/s of the individuals of the populations. The results of the study is useful in the selection of sources of good planting materials for the improvement of narra tree in the Philippines.